2007
DOI: 10.1074/jbc.m704015200
|View full text |Cite
|
Sign up to set email alerts
|

The N1317H Substitution Associated with Leber Congenital Amaurosis Results in Impaired Interdomain Packing in Human CRB1 Epidermal Growth Factor-like (EGF) Domains

Abstract: The calcium-binding epidermal growth factor-like (cbEGF) domain is a widely occurring module in proteins of diverse function. Amino acid substitutions that disrupt its structure or calcium affinity have been associated with various disorders. The extracellular portion of CRB1, the human homologue of Drosophila Crumbs, exhibits a modular domain organization that includes EGF and cbEGF domains. The N1317H substitution in the 19th cbEGF domain of CRB1 is associated with the serious visual disorder Leber congenita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Addition of Ca 2+ resulted in numerous peak shifts and intensity changes, consistent with Ca 2+ -dependent conformational changes. These features have been observed in other natively folded cbEGF constructs 25,29,31,33,35 and thus confirm that these constructs have the correct disulphide-bonded structure. The spectra for the G202R construct looked strikingly similar to those for the wild type, while some minor differences between the spectra of wild-type cbEGF2-4 and the spectra of I169T-substituted cbEGF2-4 were seen.…”
Section: Nmr Spectroscopysupporting
confidence: 73%
“…Addition of Ca 2+ resulted in numerous peak shifts and intensity changes, consistent with Ca 2+ -dependent conformational changes. These features have been observed in other natively folded cbEGF constructs 25,29,31,33,35 and thus confirm that these constructs have the correct disulphide-bonded structure. The spectra for the G202R construct looked strikingly similar to those for the wild type, while some minor differences between the spectra of wild-type cbEGF2-4 and the spectra of I169T-substituted cbEGF2-4 were seen.…”
Section: Nmr Spectroscopysupporting
confidence: 73%
“…The intracellular region that has a highly conserved role in organizing a macromolecular protein scaffold contains a conserved FERM binding domain, which is involved in localizing proteins to the plasma membrane, and a PDZ binding motif (PBM), used in the process of anchoring to the cytoskeleton. 2,3,7,16,18,19 Although no binding partners for the extracellular region have been identified so far to our knowledge, almost all identified CRB1 mutations affect this region. 1,[3][4][5]8,14 Missense mutations affecting cysteine residues are predicted to affect the secondary structure of the protein due to disruption of disulfide bridges.…”
mentioning
confidence: 99%
“…For epithelial cells and photoreceptors, separation of their apical and basal compartments is critical for proper development and function of the cells and the tissue, including adhesion and signaling between and within cells. 2,7,13,[16][17][18][19] Jacobson et al suggested that CRB1 mutations underlie developmental defects in LCA, including thickening of the retina and lack of distinct layering in the fully developed adult retina. 13 Rashbass et al postulated that CRB1 has a role in localizing phototransduction proteins to the apical membrane of the photoreceptors.…”
mentioning
confidence: 99%
See 2 more Smart Citations